UM Virtual Network Computing (UMVNC) / Kok Soo Leong - Kok , Soo Leong (2005)
UMVNC is an application for FSKTM staff. Remote controlling software such as UMVNC has a variety of uses. It allows a person at a remote computer to assume control of another computer across a network, as if they were sitting in front of the other computer. This thesis project is aimed to assist the operation and management of faculty of Computer Science and lnfonnation Technology. Network administrator or network technician can easily use UMVNC to control other PC. UMVNC can help to troubleshoot the computer of a distant less-technically-savvy relative. UMVNC can also be used in educationall contexts, for example to allow a distributed group of students simultaneously to view a computer screen being manipulated by an instructor, or to allow the instructor to take control of the students' computers to provide assistance This thesis project hns been developed on Windows XP Professional and the software development tools - Microsoft Visual Studio .NET 2003 Professional Edition. I used C#.NET to develop and enhance the features of UMVNC. It is hoped that FSKTM and University of Malaysia can use the Virtual Network Computing Application to manage the network computers. Beside that, I hope this UMVNC application will be further developed and enhance features in the future to explore more functionalities that can be offered so that it can actually be put into use.